Degumming of crude palm oil by membrane filtration - Ong, K. K.; Fakhru'l-Razi, A.; Baharin, B. S.; Hassan, M. A. (Informa UK Limited, 1999)
The application of membrane separation in palm oil refining process has potential for energy and cost savings. The conventional refining of crude palm oil results in loss of oil and a contaminated effluent. Degununing of crude palm oil by membrane technology is conducted in this study. The objective of this research is to study the feasibility of membrane filtration for the removal of phospholipids in the degumming of crude palm oil, including analyses of phosphorus content, carotene content, free fatty acids (as palmitic acid), colour and volatile matter. A PCI membrane module was used which was equipped with polyethersulfone membranes having a molecular weight cut off of 9,000 (type ES209). In this study, phosphorus content was the most important parameter monitored. The membrane effectively removed phospholipids resulting in a permeate with a phosphorus content of less than 0.3 ppm. The percentage removal of phosphorus was 96.4% and was considered as a good removal. Lovibond colour was reduced from 27R 50Y to 20R 30Y. The percentage removal of carotene was 15.8%. The removal of colour was considered good but die removal of carotene was considered insignificant by the membrane. Free fatty acids and volatile matter were not removed. Typical of membrane operations, the permeate flux decreased with time and must be improved in order to be adopted on an industrial scale. Membrane technology was found to have good potential in crude palm oil degununing. However, an appropriate method has to be developed to clean the membranes for reuse